2022
DOI: 10.4314/aas.v19i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hydatidosis in children: a different pattern from adults?

Abstract: Background: Hydatidosis is a major health problem is many countries. It is a parasitic disease that can affect adults as well as children. Hydatid cyst often involves the lungs in children. Given the anatomical and physiological differences between children and adults, generalization from adult studies is inappropriate. Methods: To determine particularities of lung echinococcosis in children, we conducted a retrospective study of all cases treated for hydatid cyst of the lung at our department. Results: One hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This is due to the high elasticity and compressibility of the lungs in children. [24][25][26] In one retrospective review of pediatric hydatid cysts from our institution, the lung was found to be the most common site of involvement in 76.5% of the children. 27 Pulmonary hydatid cyst was also the most common indication for thoracotomy in a study from Turkey in which it accounted for 35% of the procedures.…”
Section: Discussionmentioning
confidence: 97%
“…This is due to the high elasticity and compressibility of the lungs in children. [24][25][26] In one retrospective review of pediatric hydatid cysts from our institution, the lung was found to be the most common site of involvement in 76.5% of the children. 27 Pulmonary hydatid cyst was also the most common indication for thoracotomy in a study from Turkey in which it accounted for 35% of the procedures.…”
Section: Discussionmentioning
confidence: 97%